2019
DOI: 10.3390/ijms20153628
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Heme Oxygenase-1 in Atherosclerotic Diseases

Abstract: Heme oxygenase-1 (HO-1) is an intracellular enzyme that catalyzes the oxidation of heme to generate ferrous iron, carbon monoxide (CO), and biliverdin, which is subsequently converted to bilirubin. These products have anti-inflammatory, anti-oxidant, anti-apoptotic, and anti-thrombotic properties. Although HO-1 is expressed at low levels in most tissues under basal conditions, it is highly inducible in response to various pathophysiological stresses/stimuli. HO-1 induction is thus thought to be an adaptive def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 106 publications
6
56
0
Order By: Relevance
“…Heme degradation occurs in all cell types in order to complete the turnover of heme-containing proteins. Furthermore, HMOX1 induction crucially drives cell adaptive responses to stressors and its metabolic products exert potent biological activities (Siow et al, 1999;Otterbein et al, 2016;Kishimoto et al, 2019). CO has anti-apoptotic and antiinflammatory activities (Ryter et al, 2002), both intracellularly and in the microenvironment (Morita and Kourembanas, 1995) of blood vessels by increasing cGMP concentration and activating the MAPK pathway (Siow et al, 1999;Ryter et al, 2002).…”
Section: Biosynthesis Metabolism Bioavailability and Activitymentioning
confidence: 99%
“…Heme degradation occurs in all cell types in order to complete the turnover of heme-containing proteins. Furthermore, HMOX1 induction crucially drives cell adaptive responses to stressors and its metabolic products exert potent biological activities (Siow et al, 1999;Otterbein et al, 2016;Kishimoto et al, 2019). CO has anti-apoptotic and antiinflammatory activities (Ryter et al, 2002), both intracellularly and in the microenvironment (Morita and Kourembanas, 1995) of blood vessels by increasing cGMP concentration and activating the MAPK pathway (Siow et al, 1999;Ryter et al, 2002).…”
Section: Biosynthesis Metabolism Bioavailability and Activitymentioning
confidence: 99%
“…Therefore, there is an urgent need for new treatment strategies. HO-1 has been suggested as a potential therapeutic target (reviewed in [ 137 ]). HO-1 binds and degrades heme intracellularly, and the resulting degradation product bilirubin has antioxidant effects [ 138 ].…”
Section: Hemolytic Conditionsmentioning
confidence: 99%
“…In general, the level of HO-1 expression is low when cells are at the resting stage, but profoundly enhanced by certain conditions or stimulators, such as heavy metals, heme, cytokines, hormones, lipid metabolites, and oxygen status [2]. In addition, recent studies have shown that HO-1 is involved in the improvements of several events, such oxidation stress, airway inflammation, functions of adipocytes, obesity, steatohepatitis, atherosclerosis, diabetes mellitus, brain hemorrhage, as well as neuroprotection [3][4][5][6][7][8]. This is especially essential in the health maintenance of the liver which contains about 15% of body heme [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially essential in the health maintenance of the liver which contains about 15% of body heme [9][10][11][12]. Numerous studies have proved that the anti-inflammatory, antioxidant, pro-angiogenic, anti-thrombotic, and anti-apoptotic effects of HO-1 are derived from its catabolic byproducts, CO and biliverdin, which render HO-1 as a tissue protector and a good candidate for investigating new therapeutic interventions [1,8,13]. However, several studies have extensively demonstrated the positive role of HO-1 in cancer progress [14][15][16].…”
Section: Introductionmentioning
confidence: 99%